Концептуальний зміст комплексу маркетингових досліджень та його роль в системі прийняття управлінських рішень - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А. (Ways to Improve Construction Efficiency, 2013)
The role and place of marketing research in the management of universities. Has four key questions: what purpose they serve marketing research, what their conceptual content, on what the direction they are conducted and how the results of marketing research are applied in practice.